The impact of street service care on frontline service utilisation during high‐alcohol use hours in one night‐time entertainment precinct in Australia. (1st December 2019) - Taylor, Nicholas; Coomber, Kerri; Curtis, Ashlee; Mayshak, Richelle; Harries, Travis; Ferris, Jason; Patafio, Brittany; Hides, Leanne; de Andrade, Dominique; Miller, Peter
Abstract: Introduction and Aims: Street service care providers in Queensland, Australia are organisations tasked with assisting vulnerable individuals and aiding intoxicated patrons that are at risk of harm in night‐time entertainment precincts (NEP). Members of these organisations patrol NEPs and provide services, such as first aid, to individuals in need. There has been no research conducted on their impact on crime, injuries and on the duties of Australian frontline service resources (e.g. police and ambulance services). This study evaluated the introduction of a single street service care in the Cairns NEP on police‐recorded assaults, emergency department injury presentations and ambulance service utilisation during high‐alcohol hours. Design and Methods: Police‐recorded assaults (common and serious), emergency department injury presentations and ambulance attendances for the Cairns suburbs were examined. Autoregressive integrated moving average time series analyses were used to determine the impact of street service care on monthly counts for each dataset. Results: Serious assaults during high‐alcohol hours significantly declined after the introduction of the support service in Cairns, with a one‐month lagged impact ( B = −1.66, 95% confidence interval −3.02, −0.30). No other significant impact on common assaults, emergency department injury presentations or ambulance attendances were found. Discussion and Conclusions: This study provides preliminary evidence that street service care may help to decrease assaults within a single NEP. However, further research investigating the impact of street services in larger cities, and determining what other roles the service may be able to play in preventing alcohol‐related harm, is needed.